Influencia de los procesos de comunicación interactiva en el desempeño laboral de los colaboradores de la empresa postes del norte s.a. en el 2015 - Casana Cruzado, Katherine Estefany (2016)
This thesis was carried out in order to analyse and determine the relationship between interactive communication and the job performance of employees of the company posts of del Norte S.A. This has been considered the type of qualitative research, having as base the explanatory design, with which applied the methods and techniques of quantitative and qualitative research. The population was made up of employees considered as shown in its entirety. The technique used was the survey. The results show that the company posts del Norte S.A. is dominated by an atmosphere reflected a constant interactive communication authoritarian demonstrating a working environment that encourages employees who feel motivated fully by the Organization, which has been influencing their work performance. The workers of the company appear to be identified with the company, they participate in different activities generating processes through an interactive communication between coworkers, but so also manifest that the company is identified with the worker, this refers to a large extent, to the motivation to workers, existence of incentives, centralization in decision-making appropriate communication channels generating as a consequence the lack of confidence in daily activities. Finally work is presented as a contribution to the solution of a problem of great importance within the company, since it provides several alternatives to motivate the human resources and at the same time create an organizational climate for good job performance. Key words: communication and work performance